Heat transfer and energy efficiency analysis of domestic refrigerator using nanorefrigerant / Farhood Sarrafzadeh Javadi - Farhood, Sarrafzadeh Javadi (2013)
Until 200 years ago, refrigeration was achieved by natural ice from mountains. In the past fifty years, refrigeration system has experienced massive technological change. It has gone from the era of the iceman to that of the advanced technology. Nanotechnology as a modern invention can be a promising technological leap in refrigeration. Nanorefrigerant, as a new and complicated application of nanofluid in the refrigeration system remains unknown because of the complex process that happens in the refrigeration system. This study focuses on the performance of the domestic refrigerator using nanorefrigerant based on energy approach. In this study, stability of nanofluid, effects of using nanorefrigerant on refrigeration system, energy and heat transfer analysis of domestic refrigerator in case of using nanorefrigerant have been experimentally investigated. It is found that the stability of nano-lubricant oil decreases by increasing the nanoparticle concentration in basefluid (R134a). Evaporator temperature gradient is increased by increasing the nanoparticle concentration. The maximum temperature gradient increased in the evaporator was 20.2% in case of using 0.1%-Al2O3 and was about 1.9 C  . It has been found that the compressor consumes 3.821 kWh/24h by using basefluid. The results show that the energy consumption of refrigerator decreased by around 2.69% when the 0.1%-Al2O3 nanoparticle was added to the system.